Peran Entrepreneurship Education Terhadap Minat Berwirausaha Melalui Entrepreneurial Self-Efficacy Sebagai Mediasi - Ni Putu Candra Lestari; Ni Made Yudhaningsih; I Made Anom Arya Pering (CV ODIS, 2022)
The object of this research is at Mahendradata University, to analyze the role of Entrepreneurship Education on Entrepreneurial Self-Efficacy as Mediation, using a quantitative methodology with a questionnaire, with a population of 109 people and a sample of 52 respondents, namely Alumni graduates of the Faculty of Economics and Business, Mahendradata University Batch 2021. Using 4 hypotheses with SEM – PLS analysis tools. The results of this study (1) Entrepreneurship Education has a positive and significant effect on the interest in entrepreneurship, (2) Entrepreneurship Education has a positive and significant effect on Entrepreneurial Self-Efficacy, (3) Entrepreneurial Self-Efficacy has no significant positive effect on entrepreneurial interest, and (4) Entrepreneurial Self-Efficacy mediates Entrepreneurship Education and has no significant positive effect on entrepreneurial interest.